Standards in cultural heritage: the missing grammar for the digital documentation of the past - Ioannides, Marinos; Georgopoulos, Andreas; Scherer, M. (My University, 2005)
Information Technology (IT) is traditionally used in most scientific and engineering areas of study, where standards/guidelines already exist to a certain level. Many Cultural Heritage (CH) experts recognize an initial advantage of IT in their field. The revolution and e-volution of IT and the continuous expansion of this technology has set the experts of Cultural Heritage (archaeologists, restorators, renovators, civil engineers, architects, surveyors, chemists, physicists, the engineers), under massive pressure to become familiar with and use the computer technology available. These experts have begun to take advantage of IT because the data and information can be reliably read, sorted, indexed, manipulated, retrieved and communicated between different compatible and incompatible systems nationally and internationally. Due to unorganized and non standardised methods of use of these IT-tools, the achieved results are predominantly incompatible for different systems, presentations and future use. “Island solutions” have emerged limiting the study area of the researcher which leads to the incompatibility of cataloguing, archiving, presenting, visualizing and conserving archaeological documents, artefacts, monuments and sites in a unified worldwide format. This situation is a part of the result of funded EU, UNESCO, ICOMOS and other projects which achieved good results, but were not planned for future use in a European albeit worldwide context. It is a fact that there has been total lack of global specifications for recording and documenting monuments and artefacts and in general any CH item using traditional or modern technological methods. Monuments, for example, are quite diverse and hence each one should be recorded with its own specifications. On the other hand, specific, unified, worldwide standards/guidelines of general acceptance must be proposed, developed, introduced, applied, tested, accepted and adopted in order to enable specialists all over the world to address this problem with a unified approach for the benefit of CH. A standard, in Information Technology, can be defined as a set of regulations (the Grammar) for the guarantee of the correct development and protection of the long-term value of digital data for the storage, exchange, sharing, searching, visualizing/presenting and retrieval of information between different users/professionals around the world using the global computer network (Internet) and different hardware and software structures. These standards/guidelines can help all experts involved in the cultural heritage area in the restoration/ renovation/ protection/ documentation/ archiving/monitoring of the history of mankind and secure this for the future (e-Libraries, e-Museums, etc). Standards are necessary for an uncomplicated exchange of information today and for the guarantee of the protection of the long –term value of digital data/ knowledge in the future. In this paper a proposal for approaching the standards of modern technological advances in CH recording as well as documenting/monitoring is also attempted, with the hope that it will lead to a widely accepted vision for the standardization of such methods.
Keywords: Standards; Documentation; Archiving; Databases; Monitoring